Rehabilitation of Stroke Patients - Effects of Early Intervention of Physical Therapy on Functional Outcome (Bangladesh Journal of Anatomy, 2009)
Context: Early initiation of rehabilitation procedures in stroke patients can enable greater return of neurological functions and prevents complication, thereby improves long term outcome and quality of life. Functional Independence measure (FIM) score is one of the commonest scale used to measure outcome. Study design: Prospective type of study. Place of study: Dept. of Physical Medicine and Rehabilitation, BSMMU. Method: 48 acute onset first episode stroke patients were assessed Rehabilitation procedures started immediately after attending the Dept. According to a comprehensive rehabilitation plan physical therapy, speech therapy, occupational therapy was given and continued for 8 weeks, with proper education to the patient and the attendant. Result: Outcome was measured and the result showed significant improvements (p value